A SYSTEMATIC REVIEW OF LITERATURE ON THE CARE OF OLDER PEOPLE WHO FALL AND USE OUT-OF-HOSPITAL EMERGENCY SERVICES. Issue 5 (18th April 2015) - Halter, Mary; Chatters, Robin; Koniotou, Marina; Evans, Bridie
Abstract : Background: Older people who fall have been a priority area for the NHS since the publication of the National Service Framework for Older People. Evidence suggests falls prevention can reduce further falls. With rising numbers using Emergency Departments, there is a policy shift for ambulances to convey fewer patients and efforts to refer falls patients to other services Objective: To review evidence about impact and implementation of interventions delivered by emergency medical services to treat older people who fall to reduce emergency admissions to hospital. Method: We undertook a systematic literature search of 18 electronic databases and reference lists. References were downloaded into biographic software, screened by one of three researchers against pre-defined inclusion criteria. Data were systematically extracted and assessed for methodological quality; whilst narrative synthesis was used to analyze findings. Results: Through our searching and screening process we identified 12 international studies. Interventions fell into two groups: (1) on-scene screening during patient assessment or triage at 999 call to refer them for falls prevention treatment or hospital conveyance; and (2) retrospective screening and referral to fall prevention treatment. Up to half of patients screened on-scene were conveyed to hospital and referrals to falls services were low, except where undertaken automatically. One trial reported patients had fewer falls and increased confidence after undergoing rehabilitation; additionally, they found there was a significant reduction in ambulance calls over 12 months. The quality of studies was weak and data were very heterogeneous, limiting comparison and quality of results.  Discussion: Despite national priority about preventing falls and calls for reduced emergency department use, there are few studies and weak evidence about the most effective ways to support paramedics to use alternative treatments to target best treatment for older people who fall.